ANALISIS PENGGANTIAN RESISTOR DENGAN LAMPU PIJAR PADA RANGKAIAN DC MELALUI SIMULASI PhET - Widya, Dinna; Malik, Adam (Charm Sains: Jurnal Pendidikan Fisika, 2023)
This study aims to analyze the ability of incandescent lamps to replace resistors in series circuits when given a DC voltage. The research method used uses a quantitative approach. The data collection technique is through virtual experimentation on the PhET interactive simulation. The experiment was carried out twice using different treatments. The first experiment uses two resistors with the same magnitude of each resistance. The second experiment uses a resistor and an incandescent lamp with the same resistance. An incandescent lamp has the same resistance as a resistor. Through each experiment, six data on the strength of electric currents with different DC voltages were obtained. Based on the two experiments, the increase in DC voltage causes the resulting electric current to be stronger. The data obtained is then visualized in graphical form, then analyzed by regression. Based on the research results, incandescent lamps cannot replace the role of resistors in an electric circuit. This was proven when one of the resistors was replaced with an incandescent lamp producing a different electric current strength. Even though the resistance on the resistor and the incandescent lamp are the same.